Epidemiologic characteristics of injuries among 1–5 year-old children in Hamadan Province: Analysis of 4523 hospitalized children over a 6-year period - Salman Khazaei (Archives of Trauma Research, 2020)
Background: Unintentional injuries are one of the major causes of death in Iranian children. Information on epidemiological pattern of injury among one-to 5-year-old children is limited in Hamadan. The aim of this study was to clarify the person, space and time pattern of injury among 1–5-year-old children in Hamadan Province. Methods: All registered incidence cases of injury among 1–5 year-old children in Hamadan Province from March 2009 to March 2015 were included in this cross-sectional study. We analyzed the data on county, gender, age category, type of injury, season and outcome of injury. Temporal trend was explored using time series regression with accounting autocorrelation, seasonality, and short-term variation. Results: This study included 4523 injury cases. During the studied period, urban residents and boys had a higher number of injuries. Motor vehicle-related injuries were the most common type of injury. A seasonality pattern was found so that most of the cases were occurred in summer months. The lowest and highest incidence rate ratios (IRRs) were occurred in January 2011 (IRR = 0.61 with 95% confidence interval [CI]: 0.31, 1.18) and May 2014 and August 2013 (IRR = 6.78 with 95% CI: 4.38, 10.51), respectively. Conclusion: In Hamadan Province, childhood injury has a variation in person, place, and time pattern, as some groups such as boys and urban residents among 1–5 year-old children are at a higher risk for the incidence of injury. Therefore, it is recommended that health service managers and health policymakers devote more healthcare and resources to the high-risk groups.